2014
DOI: 10.1136/bjsports-2013-092928
|View full text |Cite
|
Sign up to set email alerts
|

Precooling and percooling (cooling during exercise) both improve performance in the heat: a meta-analytical review

Abstract: Background Exercise increases core body temperature (Tc), which is necessary to optimise physiological processes. However, excessive increase in Tc may impair performance and places participants at risk for the development of heat-related illnesses. Cooling is an effective strategy to attenuate the increase in Tc. This meta-analysis compares the effects of cooling before ( precooling) and during exercise ( percooling) on performance and physiological outcomes. Methods A computerised literature search, citation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
216
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(233 citation statements)
references
References 48 publications
13
216
4
Order By: Relevance
“…However, it should be acknowledged that modest changes in T CORE have the potential to modify effector thresholds such as vasomotor and sudomotor sensitivity or sweat rate (Kondo et al 2009), however this effect may necessitate sweating to have commenced, which is unlikely during IP at rest, and may explain why neither T SKIN nor sweat rate subsequently differed. Whilst the observed reduction in T CORE may be considered small in comparison to that following precooling techniques (Bongers et al 2015;Tyler et al 2015), future research may also consider how this could complement a cooling strategy prior to competing in the heat. Moreover, future research should investigate changes in whole-body blood flow in order to understand the observed change in T CORE , that appears to be independent of changes in both muscle and skin temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be acknowledged that modest changes in T CORE have the potential to modify effector thresholds such as vasomotor and sudomotor sensitivity or sweat rate (Kondo et al 2009), however this effect may necessitate sweating to have commenced, which is unlikely during IP at rest, and may explain why neither T SKIN nor sweat rate subsequently differed. Whilst the observed reduction in T CORE may be considered small in comparison to that following precooling techniques (Bongers et al 2015;Tyler et al 2015), future research may also consider how this could complement a cooling strategy prior to competing in the heat. Moreover, future research should investigate changes in whole-body blood flow in order to understand the observed change in T CORE , that appears to be independent of changes in both muscle and skin temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…24 Wearing cooling vests during exercise has shown the greatest improvement in exercise performance (20.4%), 79 whereas other evidence shows that ingesting cold water improves exercise performance by 12.4%. 80 Although cooling during exercise has shown improvements in performance, difficulties will arise when attempting to implement 1 modality across all sports due to the individual nature of each sport.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in performance from precooling focuses on the premise that lowering body temperature below its set point before exercise allows athletes to exercise at a higher intensity during exercise as they are afforded a greater temperature gradient before performance is adversely affected. 51,72,73 A recent meta-analytical review 24 found that precooling improved exercise performance by a factor of 5.7% overall, with mixed cooling methods (ie, CWI and cooling vests) providing the largest improvement in exercise performance (7.3%) Cooling postexercise has also been investigated in that cooling the body postexercise allows athletes to recover more quickly and thus have the potential to improve their performance in subsequent competition. 11,13 It is postulated that high internal thermal loads, often seen after intense exercise in the heat, result in the degradation of exercise performance and lengthen the time for the body to recover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations